Inequality and Education: A Critical Analysis of Class Theories in the Present Context - Chalaune, Bhawan Singh (Far Western Review, 2023)
The purpose of this article is to analyze how education works in Nepal based on theories related to class inequality. The paper argues that the unequal distribution of wealth and power, prestige, social discrimination and cultural hegemony creates social inequality. Karl Marx and Max Weber made significant contributions to the study of social inequality arguing that the education system is controlled by the class that has the most wealth and power. As a result, the ruling class of Nepal has not paid much attention to improving the quality of government schools to be studied by children of lower economic classes. However, the class structure is in the changing process at present. The service sector is becoming wider than the manufacturing sector. The role of the manager is stronger than that of the owner. The education system is closely related to the new class structure. Therefore, the present educational inequality cannot be understood only from the viewpoint of the traditional class system. It is necessary to understand and find solutions to the new class structure created on the basis of economic as well as cultural hegemony and administrative status in the present context of the world including Nepal. And equality and quality should be sought in education to reduce class inequality in Nepali society. For this, it is necessary to make structural changes from national policy to classroom teaching and learning.